2012
DOI: 10.1016/j.ijsu.2012.03.009
|View full text |Cite
|
Sign up to set email alerts
|

The development of an Oncoplastic Training Center – OTC

Abstract: Organized oncoplastic training centers can enable breast surgeons to undertake reconstructive breast procedures without the assistance of a plastic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…Breast surgeons should be well trained and competent in all aspects of breast oncology and have broad understanding of breast defects and all their reconstructive requirements, as well as being proficient in prevention and providing care for all potential complications. This is the challenge for present and future mentoring of breast surgeons [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Adequate local control of disease and quality of life are both deeply related to surgical decisions and skills at the moment of breast cancer diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast surgeons should be well trained and competent in all aspects of breast oncology and have broad understanding of breast defects and all their reconstructive requirements, as well as being proficient in prevention and providing care for all potential complications. This is the challenge for present and future mentoring of breast surgeons [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . Adequate local control of disease and quality of life are both deeply related to surgical decisions and skills at the moment of breast cancer diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some controversies remain in many countries about whether it is better to have breast surgeons and plastic surgeons working together, or a breast specialist doing everything in most, or indeed in all, cases. Also, surgical mentoring is a significant challenge for all specialties [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The delivery of qualified OP and reconstructive training is expected to be tailored as to meet educational needs and to be recognized internationally.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, an oncoplastic training centre was established with the approval of the Brazilian Society of Mastology. The training centre has offered a 21-module course that takes place on one weekend per month and that targets practicing breast surgeons rather than recent surgical graduates 11 .…”
Section: International Ops Trainingmentioning
confidence: 99%
“…Currently, breast surgeons dealing with breast cancer surgery are performing most OBS. It has been demonstrated that surgeons can perform many OBS applications without the need for a plastic surgeon, by learning basic plastic techniques (57). Surgeons may correct most breast defects by learning the required techniques in plastic surgery during breast cancer surgery that they have already been doing.…”
Section: Disadvantagesmentioning
confidence: 99%